Role of Pesantren in Improving Sociopreneurs of the Community Around Pesantren in Palembang City - Safitri Asrol; Nur Hesthria; Oki Sania Rizki (Peradaban Journal of Economic and Business, 2023)
The function of pesantren besides education and da'wah is community empowerment. One of the implementations of the empowerment function is the role of Pesantren in increasing Sociopreneurship in the community around the pesantren. So, this study suggests the role of pesantren in increasing the Sociopreneurship of the Islamic Boarding School Community in Palembang City. This study uses descriptive qualitative research methods and field research methods. Data collection techniques were carried out using observation, and interviews by distributing 30 questionnaires to pesantren administrators and local communities. The study found that social entrepreneurship in pesantren is carried out by providing students with the skills to run a business and collaborate with SMEs (Micro, Small, and Medium Enterprises) to develop businesses. Pesantren also provides economic assistance to socioeconomically disadvantaged populations. The development of Sociopreunership carried out by pesantren has a positive impact on the community around the pesantren, especially in improvement an living standards.